The effectiveness of using Nearpod media on the learning outcomes of grade XI students in geography subject at SMA Negeri 4 Sidrap - Nur Fadilah; Abd. Kahar; Muhammad Takdir (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to examine the effectiveness of Nearpod media in improving the Geography learning outcomes of Grade XI Social Science students at SMA Negeri 4 Sidrap. The main issue addressed is the low student motivation and participation due to monotonous teaching methods. This research employed a quantitative approach with a one-group pretest-posttest design, involving 19 students as the sample. Data were collected through tests and questionnaires, then analyzed using the mean formula. The results showed an increase in the average score from 60.5 (pre-test) to 85 (post-test). The majority of students achieved scores above the minimum passing grade (KKM) and demonstrated improvements in task completion punctuality. In conclusion, Nearpod media is effective in enhancing students' learning outcomes, comprehension, and discipline.